PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR IPA MATERI SIFAT DAN PERUBAHAN WUJUD BENDA PADA SISWA KELAS V SDN 011 KARIMUN - Hilda Oktriyeni; Evatimah; Dirneti (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2022)
The purpose of this study was to determine the effect of using the Guided Inquiry Learning Model on Science Learning Outcomes of Material Properties and Changes in Objects in Class V Elementary School 011 Karimun. This type of research is quantitative with a One-Group Pretest-Posttest Design approach. The population of this research is the fifth grade students of SD Negeri 011 Karimun, totaling 17 students. With saturated sampling technique. Data collection techniques using observation and tests. The instrument used is a multiple choice test in the form of 20 objective questions. The data analysis technique used t-test. The result of the research is that there is a significant effect using the Guided Inquiry learning model on the science learning outcomes of the Nature and Changes in Objects in class V SD Negeri 011 Karimun with the obtained tcount 11.78> ttable 2.11.